Analisis Sifat Fisika dan Kimia Lignin Tandan Kosong Kelapa Sawit asal Desa Sape, Kabupaten Sanggau, Kalimantan Barat - Siti Suhartati; Rachmat Puspito; Fikri Rizali; Dian Anggraini (Jurnal Kimia Valensi, 2016)
Analysis of the physical and chemical properties of palm empty fruit bunches (EFB) lignin from Sape village in Sanggau, West Borneo has been done. This research was aimed to find extract and isolate the EFB lignin, to determine density, and viscosity of black liquor containing EFB lignin and to find the purity, moisture content and ash content of isolated EFB lignin. Black liquor was extracted by using reflux process and the lignin was isolated by using organosolv process. The result showed that the density and viscosity of the black liquor was 0.9658 g/mL and 1.4565 Ns/m2, respectively. The isolated lignin isolated has purity about 64.64% with moisture content about 3.07% and the ash content about 30.34%. The data from this analysis became the basis of utilization of lignin TKKS in some lignin-based industries. Key words: Analysis of physical and chemical properties, lignin, EFB DOI: http://dx.doi.org/10.15408/jkv.v2i1.3102